Restorative justice in a prison community: or everything I didn't learn in kindergarten I learned in prison - Swanson, Cheryl G. (Lexington Books, 2009)
Improvement needed -- Restorative justice in prison communities -- Restorative justice goes to W.C. Holman Correctional Facility -- Learning to play with others -- Cleaning up after yourself -- Learning the ABCs -- Working with others -- Getting to the next grade -- How guardians see it -- What's next?